2020
DOI: 10.1021/acsami.0c16325
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Thin-Film Transistors with an Atomic-Layer-Deposited Indium Gallium Oxide Channel: A Cation Combinatorial Approach

Abstract: The effect of gallium (Ga) concentration on the structural evolution of atomic-layer-deposited indium gallium oxide (IGO) (In1–x Ga x O) films as high-mobility n-channel semiconducting layers was investigated. Different Ga concentrations in 10–13 nm thick In1–x Ga x O films allowed versatile phase structures to be amorphous, highly ordered, and randomly oriented crystalline by thermal annealing at either 400 or 700 °C for 1 h. Heavy Ga concentrations above 34 atom % caused a phase transformation from a polycry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 67 publications
2
56
1
Order By: Relevance
“…Recently, crystalline OSs have been proposed to enhance the carrier mobility because the disorder-induced subgap states can be suppressed via lattice ordering. Yang et al reported a μ FE value of 60.7 cm 2 V −1 s −1 for a TFT obtained using polycrystalline In–Ga–O annealed at 700 °C 31 . Although high annealing temperatures result in better electrical properties of the oxide active channel layer, such high temperatures are unsuitable for device application on glass or plastic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, crystalline OSs have been proposed to enhance the carrier mobility because the disorder-induced subgap states can be suppressed via lattice ordering. Yang et al reported a μ FE value of 60.7 cm 2 V −1 s −1 for a TFT obtained using polycrystalline In–Ga–O annealed at 700 °C 31 . Although high annealing temperatures result in better electrical properties of the oxide active channel layer, such high temperatures are unsuitable for device application on glass or plastic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Although binary metal‐oxide channel systems offer simple composition and processing, securing the high mobility and controllability of V TH and excellent I ON/OFF ratio simultaneously can be difficult. To overcome this limit of binary oxides, multi‐component oxide materials such as ternary (indium gallium oxide [IGO], 55–57 indium zinc oxide [IZO], 58–60 and zinc tin oxide [ZTO] 61,62 ) and quaternary oxide (indium gallium zinc oxide [IGZO], 63–68 and indium zinc tin oxide [IZTO] 69,70 ) species have been examined as active‐material candidates for high‐performance TFTs. The design rationale should balance mobility enhancement and carrier suppression.…”
Section: Ald‐derived N‐channel Oxide Tftsmentioning
confidence: 99%
“…Ternary IGO is an interesting active system because of its high carrier mobility and controllable microstructure, depending on the ratio between indium and gallium. Yang et al 56 described a cation combinatorial approach to creating IGO thin films by varying the ALD super‐cycle. Discernible structures in amorphous, polycrystalline, and highly aligned crystalline phases were obtained by adjusting the gallium fraction during ALD growth of IGO films and subsequent post‐annealing at 700°C, as shown in Figure 6A.…”
Section: Ald‐derived N‐channel Oxide Tftsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALD IGO has the potential for both high mobility due to the In 5s orbital and high stability from suppression of oxygen deficiency. ,, In previous research on ALD IGO, Sheng et al reported the surface reaction mechanisms of IGO using different precursor–reactant dose sequences; TFT performance was optimized (9.45 cm 2 /(V s)) when a 3InO–GaO sequence was used. Yang et al investigated the ZnO/IGO heterojunction via ALD and achieved high mobility (63.2 cm 2 /(V s)) using ZnO/IGO TFTs …”
Section: Introductionmentioning
confidence: 99%